Expression of Immunoglobulin G / Immunoglobulin M Typhoid On Neutrophil-Lymphocyte Ratio In Patients At Haji Hospital, Surabaya - Nur Zerlinda; Evy Diah Woelansari; Anita Dwi Anggraini (International Journal of Advanced Health Science and Technology, 2023)
Typhoid fever is one of the major bacterial infections worldwide caused by the bacterium Salmonella enterica serovars typhi in humans. The examination used is the rapid Typhoid test. This rapid typhoid test is used to detect antibodies to Salmonella typhi. The purpose of the study was to determine the results of the Neutrophil - Lymphocyte Ratio with various criteria results from the Immunoglobulin G / Immunoglobulin M Test in typhoid fever patients. This type of study is descriptive observational with selective sampling taken. The samples in this study were 28 samples conducted in April 2023 on typhoid fever patients at the Hajj Hospital in East Java Province. This study used the Rapid Typhoid Test Immunochromatography method with positive Widal criteria and supporting examination using Neutrophil–Lymphocyte Ratio (NLR) with Hematology Analyzer tool Fluorescent Flow Cytometry method. Typhoid and NLR rapid test results are processed descriptively in tables and based on percentages. The results obtained from the rapid test were positive IgM of 29%, positive IgG of 11%, positive IgG and IgM of 3%, and negative IgG and IgM of 57%. The average NLR was 4,43% with a median of 2,85. IgG / IgM examination of NLR showed no significant association in typhoid fever patients. It is hoped that this research will be further developed using Salmonella culture examination.